2014
DOI: 10.1007/s11150-014-9255-8
|View full text |Cite
|
Sign up to set email alerts
|

The economies of scale of living together and how they are shared: estimates based on a collective household model

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…If there is restriction about equal sharing of consumption in couples, then the counsumption of one member is: (4) Then the utility function of each member of couples is as follows: In this approach the half of returns to scale factor identifies the equivalence scale under restriction of equal sharing of consumption. It measures the proportion of the household income of a couple, which a single needs to be as well off.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is restriction about equal sharing of consumption in couples, then the counsumption of one member is: (4) Then the utility function of each member of couples is as follows: In this approach the half of returns to scale factor identifies the equivalence scale under restriction of equal sharing of consumption. It measures the proportion of the household income of a couple, which a single needs to be as well off.…”
Section: Methodsmentioning
confidence: 99%
“…According to Bütikofer and Gerfin (2009) this expression reduces to individual utility for single households given in equation (1).…”
Section: Methodsmentioning
confidence: 99%
“…The equal sharing hypothesis has already been tested and rejected by the use of data on financial satisfaction. Bütikofer and Gerfin [25], for example, estimate the effect of female income share on sharing between men and women, and Alessie et al [26] did the same for the effect of the female hourly wage ratio. They interpreted significant interaction effects for the female income contribution, in couples as a distribution factor for income sharing, and found that a higher income contribution of the female relative to her partner both increases her and lowers his financial satisfaction.…”
Section: Empirical Findings About Income Sharing From Satisfaction Datamentioning
confidence: 99%
“…For single households, this is the household income; for individuals in multi-person households, it is some share of the household income. Note that the sum of shares may exceed the household income because of the economies of scales of living together [25]. 6 According to the idea of adaptation [30], I assume that expectations about welfare levels are tailored towards the household's scope, i.e., expected welfare-effective income y * ih is a function 0 < f (.)…”
mentioning
confidence: 99%
“…It may also be distributed unequally within households based on the gender and other characteristics of each member. A large body of research has examined how personal and household characteristics-especially spouses' preferences and bargaining power-affect intrahousehold distributions of consumption expenditures (Blacklow and Ray, 2003;Browning et al, 2013;Maitra and Ray, 2005), labour supply (Mariotti et al, 2016;Rapoport et al, 2011), savings (Lee and Pocock, 2007), wealth (Grabka et al, 2015), and financial satisfaction (Bonke and Browning, 2009;Bütikofer and Gerfin, 2017). Many of these studies have used the collective household model framework (c.f.…”
Section: Introductionmentioning
confidence: 99%